Intracellular Distribution of Manganese by the Trans-Golgi Network Transporter NRAMP2 Is Critical for Photosynthesis and Cellular Redox Homeostasis. Issue 12 (27th November 2017) - Alejandro, Santiago; Cailliatte, Rémy; Alcon, Carine; Dirick, Léon; Domergue, Frédéric; Correia, David; Castaings, Loren; Briat, Jean-François; Mari, Stéphane; Curie, Catherine
Abstract : The metal transporter NRAMP2 controls photosynthesis and antioxidant defenses by releasing manganese from the trans -Golgi network, thus building up a cytosolic pool that feeds downstream organelles. Abstract: Plants require trace levels of manganese (Mn) for survival, as it is an essential cofactor in oxygen metabolism, especially O2 production via photosynthesis and the disposal of superoxide radicals. These processes occur in specialized organelles, requiring membrane-bound intracellular transporters to partition Mn between cell compartments. We identified an Arabidopsis thaliana member of the NRAMP family of divalent metal transporters, NRAMP2, which functions in the intracellular distribution of Mn. Two knockdown alleles of NRAMP2 showed decreased activity of photosystem II and increased oxidative stress under Mn-deficient conditions, yet total Mn content remained unchanged. At the subcellular level, these phenotypes were associated with a loss of Mn content in vacuoles and chloroplasts. NRAMP2 was able to rescue the mitochondrial yeast mutant mtm1∆ . In plants, NRAMP2 is a resident protein of the trans -Golgi network. NRAMP2 may act indirectly on downstream organelles by building up a cytosolic pool that is used to feed target compartments. Moreover, not only does the nramp2 mutant accumulate superoxide ions, but NRAMP2 can functionally replace cytosolic superoxide dismutase in yeast, indicating that the pool of Mn displaced by NRAMP2 is required for the detoxification of reactive oxygen species.